2015
DOI: 10.1890/14-1005.1
|View full text |Cite
|
Sign up to set email alerts
|

Naturalization of central European plants in North America: species traits, habitats, propagule pressure, residence time

Abstract: The factors that promote invasive behavior in introduced plant species occur across many scales of biological and ecological organization. Factors that act at relatively small scales, for example, the evolution of biological traits associated with invasiveness, scale up to shape species distributions among different climates and habitats, as well as other characteristics linked to invasion, such as attractiveness for cultivation (and by extension propagule pressure). To identify drivers of invasion it is there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
219
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(252 citation statements)
references
References 85 publications
20
219
0
Order By: Relevance
“…van Kleunen et al (2007) showed for a comprehensive data set of 1036 species of Iridaceae native to southern Africa that international horticultural usage was more likely for species with a larger native range, a lower maximal altitude in southern Africa and a greater height. Similarly, Pysek et al (2014) found that Central European species with a greater height and bigger propagules were more likely to be used in cultivation both in their native range and in North America. Second, the sink-region approach (sensu Pysek et al 2004) tests how alien species, irrespective of whether they are invasive or not, deviate from native species in the introduced region.…”
Section: Q@omentioning
confidence: 88%
“…van Kleunen et al (2007) showed for a comprehensive data set of 1036 species of Iridaceae native to southern Africa that international horticultural usage was more likely for species with a larger native range, a lower maximal altitude in southern Africa and a greater height. Similarly, Pysek et al (2014) found that Central European species with a greater height and bigger propagules were more likely to be used in cultivation both in their native range and in North America. Second, the sink-region approach (sensu Pysek et al 2004) tests how alien species, irrespective of whether they are invasive or not, deviate from native species in the introduced region.…”
Section: Q@omentioning
confidence: 88%
“…In MICE, parameters can be pooled across datasets to produce unbiased estimates and standard errors, providing a natural way to take into account the additional uncertainty introduced in the analysis by the presence of missing data, and to avoid circularity effects (van Buuren, 2012). However, ecological studies using multiple imputation approaches usually only apply the imputation step (Baraloto et al, 2010;Paine et al, 2011;Pyšek et al, 2015;Díaz et al, 2016) and do not take advantage of the multiple imputation framework to quantify the uncertainty resulting from the presence of missing data (but see Fisher et al, 2003).…”
Section: R Poyatos Et Al: Gap-filling a Spatially Explicit Plant Trmentioning
confidence: 99%
“…While forest inventories have adopted statistical imputation methods for some time, as for example the kNN methods (Eskelson et al, 2009, and references therein), imputation methods have only recently started to be used in traitbased ecology (Baraloto et al, 2010;Pyšek et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is far from the truth that historical data on bird introductions are poor. Our paper demonstrates that the quantity and quality of historical information may be much higher than has been argued, which can potentially improve the precision of analyses based on it (Pyšek et al 2015). Rather, they are simply hard work to unearth.…”
Section: Discussionmentioning
confidence: 79%